Development of Garbage Collection Lake Bin and Water Quality Checker with Blynk Application - Irwan, Norallisya Sazlin Binti; Misman, Dalila (Progress in Engineering Application and Technology, 2023)
The goal of this project is to create a prototype that will clean up the lake and without using the energy of the people. By using this product, it will make lake will clean without any garbage on the surface water. Both software and hardware are used in this product. This project also includes a sensor that detects waste on the water’s surface, and the boat will go to the garbage area to collect it with bin on the bottom of boat. Furthermore, Node MCU is used in this project to create a Real Time Water Quality in Lakes with IoT Application. The Wi-Fi microcontroller ESP 8266 was used. It acts as the main processing component for the project. It can only be operated by a smartphone and is remote-controllable from a great distance. It will be using temperature and humidity sensor, turbidity sensor and TDS sensor to check the water quality. The project’s IoT application will make monitoring water quality easier by allowing the water condition to be displayed remotely. This system will include smartphone as a platform to connect each other.